Vibrational Normal Modes Investigation of 4-Methyl Triazole [4,5-c] Pyridine Using Density Function Theory (DFT)-Chemical Quantum Calculation: Computer Simulation Program (Sebha University Conference Proceedings, 2024)
Fourier transform IR and Raman spectra, vibrational energy level, and potential energy distribution (PED) of 1H- and 3H-4-methyl-1,2,3-triazolo[4,5-c]pyridine tautomers, have been determined using density function theory (DFT) at the B3LYP/6-31G(d,p) level. The results of experimental values obtained an agreement with the theoretical model of geometry and vibration levels, the optimised bond lengths and bond angles are in good agreement with X-ray data of other triazole-pyridine compounds.